2012
DOI: 10.1002/pro.2178
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity of a human IgG1 anticitrullinated fibrinogen monoclonal antibody to a citrullinated profilaggrin peptide

Abstract: Rheumatoid arthritis (RA) is the most common autoimmune rheumatic disease. It is characterized by persistent joint inflammation, resulting in loss of joint function, morbidity and premature mortality. The presence of antibodies against citrullinated proteins is a characteristic feature of RA and up to 70% of RA patients are anticitrullinated protein antibody (ACPA) positive. ACPA responses have been widely studied and are suggested to be heterogeneous, favoring antibody cross-reactivity to citrullinated protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 40 publications
9
48
1
Order By: Relevance
“…Identifying a reactive region in amino acid residues 228–245, a cyclic and a linear peptide version were generated, however the two peptides showed similar characteristics [39]. These findings are in accordance to studies by Trier et al , describing the cross-reactivity of a human IgG 1 anti-citrullinated fibrinogen monoclonal antibody to cyclic and linear CCP1-derived truncated peptides [41]. …”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Identifying a reactive region in amino acid residues 228–245, a cyclic and a linear peptide version were generated, however the two peptides showed similar characteristics [39]. These findings are in accordance to studies by Trier et al , describing the cross-reactivity of a human IgG 1 anti-citrullinated fibrinogen monoclonal antibody to cyclic and linear CCP1-derived truncated peptides [41]. …”
Section: Introductionsupporting
confidence: 68%
“…Thorough analysis of citrullinated epitopes reveal that peptide backbone primarily in combination with a Cit-Gly motif is essential for reactivity, although occasionally other amino acids are tolerated C-terminal to Cit [41]. Screenings of several epitopes prior to this study indicated that especially charged amino acids C-terminal to Cit are essential for antibody reactivity (data not shown) [41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactivity of ACPA is found to be governed by the conformational flexibility of the antigenic region and the amino acid residues surrounding the citrulline. The presence of a neutral amino acid with no or a small side chain (glycine and serine) on the N-terminal site of the citrulline often favors recognition as compared with rigid residues (proline) at this position (33). In agreement with these observations, there is a glycine residue next to the citrulline in the "RG-TG(CIT)" motif preferred by ACC1.…”
Section: Discussionmentioning
confidence: 62%